The Influence of Critical Factors on Customer Retention in Islamic Banking - Gunawan, Dedi; Hanafi, Syafiq Mahmadah; Amal, Muhammad Ahsanul (Li Falah: Journal of Islamic Economics and Business, 2024)
This study aims to examine the key determinants of customer retention in Islamic banking, with a specific focus on Bank NTB Syariah. Five critical factors are analyzed: trust, Islamic business ethics, relationship marketing, service quality, and customer satisfaction. Using a quantitative approach, the research applies Stuctural Equation Modeling (SEM) with Partial Least Square (PLS) method to analyze survey data collected from 220 customers. The results indicate that trust, Islamic business ethics, and relationship marketing significantly and positively influence customer retention. Conversely, service quality and customer satisfaction were found to have no siginificant effect. These findings highlight that ethical compliance and strong relational ties are more influential than traditional service attributes in shaping customer loyalty within Islamic banking. The study contributes to the literature by integrating ethical and relational perspectives into models of customer retention and provides practical guidance for Islamic banks to strengthen customer loyalty through trust-building, adherence to Islamic ethics, and relationship marketing strategis.